2019
DOI: 10.15243/jdmlm.2019.062.1569
|View full text |Cite
|
Sign up to set email alerts
|

Effects of integrated use of grass strip and soil bund on soil properties, Southern Ethiopia

Abstract: Soil degradation is the major environmental and agricultural production problem in the highlands of Ethiopia. The objectives of the study were to examine farmers' use of grass strip and soil bund to minimize soil degradation, and effects of grass strip and soil bund on basic soil properties. Structured questionnaire survey and field observations were conducted to collect data on farmers' use of grass strips and soil bund to minimize soil erosion, improve soil fertility and crop productivity. Simultaneously, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…More sand material remains in the upper slope positions due to the removal of clay fraction from the upper slope positions and depositing it on the lower slope positions. is was in line with Umer et al [15], who reported that at the upper slope position, the soil bund managed with grass strips had better clay than the soil bund alone. Soil bunds stabilized with grass contribute a higher proportion of clay particles than the bund alone [37] and fine materials are selectively removed from the upper slope and deposited on the lower slope [38].…”
Section: Soil Physical Propertiessupporting
confidence: 92%
See 2 more Smart Citations
“…More sand material remains in the upper slope positions due to the removal of clay fraction from the upper slope positions and depositing it on the lower slope positions. is was in line with Umer et al [15], who reported that at the upper slope position, the soil bund managed with grass strips had better clay than the soil bund alone. Soil bunds stabilized with grass contribute a higher proportion of clay particles than the bund alone [37] and fine materials are selectively removed from the upper slope and deposited on the lower slope [38].…”
Section: Soil Physical Propertiessupporting
confidence: 92%
“…e soil bund with desho grass may reduce the probability of evaporation by increasing surface cover, and down movement of soil nutrients along the slope positions resulted in a high deposition of soil materials in the lower slopes which contribute the greatest amount of soil moisture content recorded under soil bund with desho grass of the lower slope. e root systems of the desho grass conserve soil moisture through minimizing erosion, evaporation, surface runoff, and modifying soil microenvironment [15,21], and variations in topography conservation measures and soil attributes affect the distribution of soil moisture content. 3, the mean value of soil pH (p ≤ 0.05) was significantly different between both SWC measures (soil bund with desho grass and soil bund only).…”
Section: Soil Moisture Content (Smc)mentioning
confidence: 99%
See 1 more Smart Citation
“…This species has been used for improving pasture quality, in soil remediation and erosion control ( Asmare et al 2016 ; Umer et al 2019 ; Kumar and Fulekar 2022 ). It was introduced to Thailand from India for forage.…”
Section: Taxonomic Treatmentmentioning
confidence: 99%
“…e main challenges of soil management practices in Ethiopia include an emphasis on physical measures (soil bunds, Fanya-juu, and so on), implementing uniform technologies for all agro-ecologies, a failure to integrate physical measures with biological practices, a top-down extension approach, and a lack of attention to indigenous knowledge [13,14]. Because of the issues presented, soil management initiatives in Ethiopia, particularly the Wera sub-watershed, have been less successful.…”
Section: Introductionmentioning
confidence: 99%